ANTIMICROBIAL RESISTANCE OF ESCHERICHIA COLI THAT ISOLATED FROM FECAL SAMPLES OF BALI CATTLE AT LOCAL FARM ON LOMBOK ISLAND - Gunawan; Seli Nurmayani; Jayanti Mandrasari; Kunti Tirtasari; Kholik (JURNAL SANGKAREANG MATARAM, 2018)
Lombok Province has Earth of Million Cattle Program. Antibiotic resistance that caused by miss antibiotic used is a major problem in the world. The aim of this study was to the isolation of Escherichia coli and their resistance of Antibiotic from fecal samples of Bali cattle of the Local farm on Lombok Island to prevent an economic loss that caused by ineffective of treatment and to antibiotic resistance in cattle and human. An observational survey with explorative laboratory was conducted in this study. Fecal samples were collected during July 2018. A fecal sample was taken by rectal exploration. Thus fecal sample was put into Brain Infusion Heart tube media by cotton swabs and they were incubated at 37℃ for 24 h to produce colony growth. The bacterial colonies were streaked on Petri dishes containing Eosin Methylene Blue Agar and then incubated for 24 h at 37°C. The purified bacterial cultures were done using Gram staining and biochemical test. The E. coli isolated were performed by a standard National Committee for Clinical Laboratory Standards (NCCLS) disk diffusion method. The result of this study showed that 94.4% E. coli isolates were resistance of Erythromycin, 61.1% were resistance of Erythromycin of Tetracycline, and 16.7% were resistance of Ciprofloxacin of 20 E.coli were isolated.